Sikap Bidan Dengan Kepuasan Ibu Dalam Pelayanan Antenatal Care - Fahma Aulia Makmur; Wiwin Hindriyawati; Diah Yuliantina (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2016)
Background The persistently high Maternal Mortality Rate ( MMR ) is 461 per 100,000 live births tend to be difficultto achieve the MDGs. Regularly monitoring actual pregnancy can guarantee access to a simple and inexpensivetreatment that can prevent maternal death in Indonesia (the world average of 13 %). Patient’s satisfaction should bemaintained if all health institutions if it is to continue to exist in health care. Comfortable service with a good attitudeand positive of health care can help the patient to get well. The results showed the majority of pregnant women doprenatal care in qualified health personnel.Research Knowing the attitude of a midwife relationship with maternal satisfaction in antenatal care services onBPS Hajaroh Srigading Bantul 2015.Research Methods This research is a descriptive correlation study. This study was conducted in BPS HajarohSrigading Bantul. The number of respondents 28 pregnant women , and using the analysis of Kendall’s Tau.Research Result The attitude of midwife in BPS Hajaroh considered sufficient except good value with 19 respondents (67,9%), very good value with 9 respondents (32,1%) and pregnant women in antenatal care services exceptsatisfied value with 24 respondents (85,7%), very satisfied value with 4 respondents (14,3%) and all of them weresatisfied with the value of 0.593 with sig (Pvalue) of 0.002.Conclusion There is a relationship of midwives attitude with satisfaction of pregnant maternal in antenatal careservices on BPS Hajaroh Srigading Bantul 2015.Keywords Attitude, Satisfaction, Antenatal Care